2009
DOI: 10.1038/ismej.2009.113
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution of cyanobacterial ecotypes in the cold biosphere

Abstract: Perennially cold habitats are diminishing as a result of climate change; however, little is known of the diversity or biogeography of microbes that thrive in such environments. Here we use targeted 16S rRNA gene surveys to evaluate the global affinities of cold-dwelling cyanobacteria from lake, stream and ice communities living at the northern limit of High Arctic Canada. Pigment signature analysis by HPLC confirmed the dominance of cyanobacteria in the phototrophic communities of these High Arctic microbial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
156
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(180 citation statements)
references
References 52 publications
22
156
2
Order By: Relevance
“…We conclude that the microbiota of both polar regions may be more connected than previously assumed and our data suggest a biogeographical connection between both poles, consistent with some previous studies Jungblut et al, 2010;Chrismas et al, 2015;Cox et al, 2016;Biersma et al, 2017;Mohit et al, 2017). The polar microbial communities in our study are an assemblage of ubiquitously-distributed and potentially endemic taxa.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We conclude that the microbiota of both polar regions may be more connected than previously assumed and our data suggest a biogeographical connection between both poles, consistent with some previous studies Jungblut et al, 2010;Chrismas et al, 2015;Cox et al, 2016;Biersma et al, 2017;Mohit et al, 2017). The polar microbial communities in our study are an assemblage of ubiquitously-distributed and potentially endemic taxa.…”
Section: Discussionsupporting
confidence: 81%
“…DNA extracts were stored frozen (−20 • C) for no longer than three months before subsequent processing. Samples from Northern Canada were extracted as described in Jungblut et al (2010), dried and stored frozen.…”
Section: Dna Extraction and 16s Rrna Gene Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, 16S-23S ITS phylogenies of the freshwater, planktic cyanobacterium Microcystis aeruginosa revealed no connection between geographic position and a placement in phylogeny (van Gremberghe et al 2011). Further, no geographical patterning has been observed in polar cyanobacteria based on 16S rRNA (Jungblut et al 2010). Taken together, the role of geographical isolation as it relates to the speciation of microbes should be further investigated using whole genome data or using more variable genome regions (Ramette and Tiedje 2007).…”
Section: Speciation Factors In (Cyano)bacteriamentioning
confidence: 99%
“…Recent studies have shown that polar and alpine regions harbor a flora that is in part composed of typical cold-adapted microbes (Jungblut et al 2009;Souffreau et al 2013), including taxa that are (potentially) endemic to Antarctica (Sabbe et al 2003;Taton et al 2006a). Many of these regions have recently entered a period of rapid warming, which has already had an impact on the physical and chemical structure, biodiversity and functioning of their aquatic ecosystems (Quayle et al 2002;Smol et al 2005;Smol and Douglas 2007).…”
Section: Introductionmentioning
confidence: 99%